PELAKSANAAN PEMBERIAN IZIN USAHA SEKOLAH MENGEMUDI DI KOTA PEKANBARU - Christine, Debby; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The development of a city marked by the increasing amount of vehicles. Along with that possession of the driver license are indispensable. To obtain a driver license, the driver must have a driving competency can be acquired through education and training common in driving schools. With all the benefits from driving school, certainly it can be used as income for the entrepreneur. Observing the development of Pekanbaru that has become the target for any entrepreneur in making businesses or to develop bussinesses, it is not missed. And the number of driving schools that exist in Pekanbaru city, proves that this business is very promising.This research aims to look at the implementation of business license driving school in Pekanbaru city and along with the obstacle factors. This research using descriptive qualitative methods of analysis which is explain the occurrence of the phenomenon. In data collection, researchers using observation and interview with the informant as an object information that is aimed for getting information in research. The kind of data that used in this research is primary data and secondary data.From the research results obtained are still many driving schools that donât have permission so the implementation license can not be said good yet. The obstacle factors include the awareness of driving school entrepreneur to register his business, the process of arrangement letter that takes too long and the lack of benefits received by driving school entrepreneur have a business license.Keywords : Implementation, License, Driving School, Business